Hierarchical modeling of energy systems - Voropai, N. I. (Nikolai Ivanovich); Stennikov, Valery A. (Elsevier, 2023)
Hierarchical Modeling of Energy Systems presents a detailed methodology for hierarchical modeling of large-scale complex systems with a focus on energy systems and their expansion planning and control. General methodological principles of hierarchical modeling are analyzed, and based on this analysis, a generalized technology for the hierarchical approach is presented. The mathematical foundations of decomposition and bi-level programming, as well as the possibility of using information technologies are also considered. The theoretical propositions are demonstrated by numerous hierarchical modeling examples aimed at planning the development of the energy sector and expansion of energy systems, analyzing, and optimizing these systems, and controlling their operation. In addition, codes and sample simulations are included throughout. This is an invaluable guide for researchers, engineers, and other specialists involved in the development, control and management of energy systems, while the summary of fundamental principles and concepts in energy modeling makes this an accessible learning tool for graduate students on any course involving energy systems or energy modeling.